‘Overcoming the barriers to engagement’: a study of the relationships between Youth Justice Service caseworkers and young men who offend - Booth, Allan (2019)
This thesis presents findings from an ESRC-funded doctoral study on the formation and ongoing maintenance of the relationship between local authority Youth Justice Service caseworkers and young men on their caseload. The dominant youth justice literature discusses community supervision as a technical and bureaucratic exercise but there is little attention paid to the emotional labour dynamics during face-to-face contacts. Twenty participants; 9 young men and 11 caseworkers were interviewed for this study. A phenomenological approach was taken to guide conversations to reflect each participant’s personal experiences of face-to-face contact. These personal reflective accounts of young men and caseworkers offered empirically informed insights into the concept of engagement through specific examples of real-life encounters. All participants were from one local authority youth justice service. It will be shown that most young men started from a position of scepticism before the first contact but that they, largely, ended up working co-operatively and actively with their caseworker. In tracking this journey, it was found that securing engagement was a subtle process of interactions that directly affected the foundation from which behaviour changes can be attempted. During this process, specific behaviours were enacted that tested the commitment of caseworkers by implicitly demanding trust, genuineness and consistency. The thesis concludes that the youth justice literature is not necessarily fully reflective of practice. To counter this, a more thorough understanding of emotional engagement during practice needs to be represented.